Introducing Different Cherry Cultivars to Inner and Crossover Areas - Hasan Sarısu; Ömer Faruk Karamürsel; Fatma Pınar Öztürk; İsmail Demirtaş; Hakkı Koçal; İbrahim Gür; Özlem Cengiz; İsmail Şevik (Journal of Agricultural Sciences)
This study was carried out to evaluate quality, yield and phenology of some sweet cherry cultivars with different maturation periods in Isparta-Egirdir conditions. The study was carried out between 2000 and 2011, on Veysel, Précoce Bernard, Star, Venus, Mechlain Haimer, Summit, Techlovan, Fercer Arcina, Sylvia, Noire de Meched, Oktavia, Belge, 0900 Ziraat, Kordia, and Ferbolus. Venus, Bernard, Techlovan and Star cultivars were identified as the earliest blooming. Oktavia, Belge, Kordia and 0900 Ziraat cultivars were found to be the latest blooming cultivars. Generally; Veysel, Bernard and Star come to harvest maturity first. Venus, Mechlain Haimer, Summit, Techlovan, Fercer Arcina, Sylvia were found to be middle season cultivars, while N. De Meched, Oktavia, Belge, 0900 Ziraat, Kordia and Ferbolus were found to be the latest. Veysel early cherry cultivar were determined to be the most productive one, while late cultivar N. De Meched and mid-season cultivar Techlovan were also found to be very efficient. In terms of fruit sizes; early sweet cherry cultivar P. Bernard, mid-season cultivar Summit and late season cultivar 0900 Ziraat gave the biggest fruits.